2017
DOI: 10.12669/pjms.333.12808
|View full text |Cite
|
Sign up to set email alerts
|

Examining the postural awareness and flexibility changes in physical therapy students who took clinical Pilates class

Abstract: Objective:This study aimed to evaluate postural awareness and changes in posture and flexibility of students who took Clinical Pilates class as an elective course at the undergraduate level.Methods:The study conducted from 2013-2016 included 98 students who took Clinical Pilates class at the Department of Physical Therapy and Rehabilitation, School of Health Sciences, Istanbul Medipol University, Turkey. The flexibility levels of the study participants were measured before and after the Clinical Pilates educat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
1
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 15 publications
1
1
0
5
Order By: Relevance
“…22 In a similar study made by Atılgan et al, university students that applied Pilates during a semester showed improvement in body awareness and flexibility scores. 23 Although there was also a control group in our study; similar to these results, we found that individuals who performed regular Reformer Pilates had better body awareness scores.…”
Section: Discussionsupporting
confidence: 87%
“…22 In a similar study made by Atılgan et al, university students that applied Pilates during a semester showed improvement in body awareness and flexibility scores. 23 Although there was also a control group in our study; similar to these results, we found that individuals who performed regular Reformer Pilates had better body awareness scores.…”
Section: Discussionsupporting
confidence: 87%
“…[24][25][26] PE/PEGs were developed by Joseph Hubertus Pilates in the 1920s and were initially called Contrology. [27] Pilates is a type of whole-body exercise aiming to develop better body awareness and functional, improved posture and breathing [26,28] In addition, the Pilates program become a superior choice for exercise weight loss in the female patient population due to its obvious burning fat effect [29,30] enhance core strength [31,32] correcting poor posture [33,34] relieve joint damage and delay spinal damage. [35,36] At present, several meta-analyses and systematic reviews have demonstrated that Pilates can achieve a moderate to large ES (standardized mean differences [SMD]: 0.62; 0.83) in the treatment of depression.…”
Section: Introductionmentioning
confidence: 99%
“…É uma prática física que promove bem-estar de maneira geral, que favorece o desenvolvimento de força, flexibilidade, percepção de movimento, melhora de equilíbrios estáticos e dinâmicos. Também possibilita a percepção corporal por meio da concentração, movimentos controlados e promoção do recrutamento muscular profundo sem exigir um esforço intenso (ATILGAN, et al 2017;ROH, 2018;SALTAN, ANKARALI, 2021).…”
Section: Introductionunclassified
“…Ademais, o ambiente universitário expõe os estudantes ao desenvolvimento de disfunções musculares e posturais devido a longa permanência em posições inadequadas, como posturas anteriorizadas e mal alinhamento dos Brazilian Journal of Health Review, Curitiba, v. 6, n. 5, p. 23517-23535, sep./oct., 2023 ombros acarretando em prejuízos musculoesqueléticos que podem passar despercebidos e ocasionar prejuízos funcionais. (BRANDALISE, et al 2021;ATILGAN, et al 2017;SALTAN, ANKARALI, 2021).…”
Section: Introductionunclassified